Short duration high-intensity interval training improves aerobic conditioning of female college soccer players - Rowan, A. E.; Kueffner, T. E.; Stavrianeas, S. (International Journal of Exercise Science, 2012)
We hypothesized that High-intensity Interval Training (HIIT) is comparable to traditional endurance training for improving aerobic capacity over a 5-week training period. A VO2max test and Yo-Yo Intermittent Recovery 1 test (Yo-Yo) were conducted by the HIIT group (Sprint Training (SPR); 5 maximal sprint efforts with 30 seconds of stimulus and 4.5 minutes of active recovery, twice weekly) and the endurance group (END; 40-min run at 80% of VO2max, twice weekly) before and after intervention. Following initial testing, female NCAA D-III level soccer players were matched for VO2max and randomly assigned to SPR (n=7) or END (n=6) groups. Between-group (END vs. SPR) and between-condition (pre- vs. post- training) comparisons were made using repeated measures ANOVA (a=0.05) with a Tukey post-hoc analysis. The Yo-Yo test revealed significant team pre- and post- training differences (1680±480 m vs. 1895±524 m respectively, p=0.002), also true for SPR (1857±423 m vs. 2131±436 m, p=0.001) and END groups (1473±494 m vs. 1613±510 m, p=0.042). There were no differences between groups for the pre-test (p=0.108) or the post-test (p=0.076). The training program resulted in significant improvements in team VO2max values (50.66±3.52 ml·kg-1 ·min-1 vs. 52.71±3.24 ml·kg-1 ·min-1 respectively, p=0.002), with no differences between the two groups for the pre- (p=0.493) and post- tests (p=0.362). The mean VO2max improved by 2.36 ml·kg-1·min-1 (4.73%) for SPR and 1.66 ml·kg-1·min-1 (3.42%) for END. Performing HIIT as little as twice per week offers an adequate aerobic training stimulus at considerable time savings.